Pelatihan Desain Menggunakan Software SolidWorks dan 3D Printing untuk Siswa SMK - Prasetyo, Rian; Lestari, Mathilda Sri; Komariah, Ainur; Suprapto, Suprapto; Sari, Maria Puspita (Universitas Islam Indonesia, 2025)
Digital technology, especially SolidWorks software and 3D printing, has brought significant changes to the modern manufacturing industry, increasing efficiency, productivity, and product quality. The problems faced by vocational school graduates are related to their lack of skills in operating the software. Community service activities aim to provide solutions, with direct training, to overcome the skills gap that arises due to the lack of facilities and competent teachers in the vocational school environment. Training methods include delivering material with practical exercises and using evaluations to measure participants' understanding. The main goal is to improve product design skills using SolidWorks and operating 3D printing machines. Based on the training carried out, it shows an increase in participants' knowledge regarding the operation of SolidWorks software and 3D printing. This can be seen from the increase in post-test scores of 6.34% compared to the pre-test. In addition, the participants' 3D printed parts showed better quality in terms of dimensional accuracy, visual surface roughness, and fewer defective parts compared to before the training.